Revision of Species in Sicyopterus (Gobiidae: Sicydiinae) Described by de Beaufort (1912), with a First Record of Sicyopterus longifilis from Japan - Maeda, Ken; Saeki, Toshifumi (Species Diversity, 2018)
Amphidromous gobies of Sicyopterus (Gobiidae: Sicydiinae) are distributed in tropical, subtropical, and temperate streams in the Indo-Pacific region. Two species, Sicyopterus japonicus (Tanaka, 1909) and Sicyopterus lagocephalus (Pallas, 1770), are known from Japan. In the present study, two specimens of an additional species were collected in Okinawa Island, in southern Japan. We compared morphologies of the type series of Sicyopterus longifilis de Beaufort, 1912 and Sicyopterus brevis de Beaufort, 1912 collected in Indonesia, with the specimens from Okinawa Island to revise the taxonomy of these species and to identify the Okinawan specimens. Syntypes of S. longifilis and S. brevis share many characters, including a unique mouth morphology. Although fin morphologies, tooth number, and the shape of the urogenital papilla differ between S. longifilis and S. brevis syntypes, these amount to normal sexual dimorphism of sicydiine gobies. De Beaufort collected his specimens at the same locality on the same date. We conclude that the syntypes of S. longifilis and S. brevis are actually males and females of same species. Therefore, they are subjective synonyms, and we give precedence to the name S. longifilis as the first reviser under Article 24.2 of the International Code of Zoological Nomenclature (International Commission on Zoological Nomenclature 1999). The two specimens from Okinawa Island were identified as S. longifilis and this is the first record of this species from Japan.